Strategies to Deal With Suicide and Non-suicidal Self-Injury in Borderline Personality Disorder, the Case of DBT - Prada, Paco; Perroud, Nader; Rüfenacht, Eva; Nicastro, Rosetta (Frontiers in Psychology, 2018)
One of the most problematic aspects of borderline personality disorder resides in repeated nonsuicidal self-injury (NSSI) and suicide attempts. These behaviours constitute the prime therapeutic target and a factor that complicates patient care, namely in terms of therapeutic continuity. It has been demonstrated that Dialectical Behaviour Therapy (DBT) is efficient in reducing the symptomatology of this disorder, as well as NSSI and suicide. DBT is a multi-component psychotherapeutic treatment, and the effectiveness of its individual constituents is therefore a relevant question. Studies comparing its various components (individual therapy, group therapy and standard DBT) have not revealed any marked difference between them, other than a tendency towards improved patient retention rates in the standard version of the treatment. The aim of this study is to review the various components of DBT and their constituent parts, in order to highlight the importance of focusing on self-harm behaviours within the therapy as a whole. Although therapeutic strategies may differ and target directly suicide or NSSI, managing the quality of life and the persistence of the therapeutic alliance (and of the interpersonal alliance) is equally important in terms of treatment efficacy.